Factors that influence the decision of Peruvian women to become entrepreneurs - Vásquez-Pauca, Marco Antonio; Zuñiga Vasquez, María Emma; Castillo-Acobo, Roxana Yolanda; Arias Gonzáles, José Luis (Revista Venezolana de Gerencia, 2022)
This study aims to discover the various entrepreneurial motives driving Peruvian women’s decision to become entrepreneurs rather than workers under the conceptual framework of the push-pull theory. For this study, researchers conducted an exploratory cross-sectional investigation to determine what factors are most likely to encourage Peruvian women to establish their businesses in their home country. Semi-structured interviews were conducted utilizing face-to-face technique. Additionally, the snowball sampling approach was used to identify possible focus group participants. Among Peruvian women’s entrepreneurial choices, personal growth, social mission, and interpersonal relationships were the most influential factors. Although financial motivation is an important factor for female entrepreneurs, it isn’t the primary driver. A larger sample of female entrepreneurs is required for the study to be generalizable. Because Peruvian women have one of the highest rates of entrepreneurial activity globally, the country’s economy might undergo a significant transformation if these women are given adequate assistance.